A Simple Surgical Technique to Repair Large Iridodialysis - Manpreet Kaur; Ashish Bajaj; Madhavi Sharma (Delhi Journal of Ophthalmology)
A large and clinically symptomatic iridodialysis often requires surgical repair. In literature, many complex and surgically complicated techniques have been described which are not possible for a general ophthalmologist to replicate in routine operation theater settings. We describe a simple technique of repairing a large iatrogenic iridodialysis and implantation of a posterior-iris-fixated intraocular lens (IOL) in a single-sitting. We found it to be a safe, less traumatic, simple surgery which requires minimum instrumentation, provides maximum patient comfort and has satisfactory cosmetic results.